Diagnosis, Evaluation, and Management of the Hypertensive Disorders of Pregnancy: Executive Summary - Magee, Laura A.; Pels, Anouk; Helewa, Michael; Rey, Evelyne; von Dadelszen, Peter; Magee, Laura A.; Audibert, Francois; Bujold, Emmanuel; Côté, Anne-Marie; Douglas, Myrtle Joanne; Eastabrook, Genevieve; Firoz, Tabassum; et al. (Journal of obstetrics and gynaecology Canada, 2014)
This executive summary presents in brief the current evidence assessed in the clinical practice guideline prepared by the Canadian Hypertensive Disorders of Pregnancy Working Group and published by Pregnancy Hypertension (http://www.pregnancyhypertension.org/article/S2210-7789(14)00004-X/fulltext) to provide a reasonable approach to the diagnosis, evaluation, and treatment of the hypertensive disorders of pregnancy. Published literature was retrieved through searches of Medline, CINAHL, and The Cochrane Library in March 2012 using appropriate controlled vocabulary (e.g., pregnancy, hypertension, pre-eclampsia, pregnancy toxemias) and key words (e.g., diagnosis, evaluation, classification, prediction, prevention, prognosis, treatment, postpartum follow-up). Results were restricted to systematic reviews, randomized control trials, controlled clinical trials, and observational studies published in French or English between January 2006 and February 2012. Searches were updated on a regular basis and incorporated in the guideline to September 2013. Grey (unpublished) literature was identified through searching the websites of health technology assessment and health technology-related agencies, clinical practice guideline collections, clinical trial registries, and national and international medical specialty societies. The quality of evidence in the guideline summarized here was rated using the criteria described in the Report of the Canadian Task Force on Preventative Health Care (Table 1).